Revision of Aphelagathis (Hymenoptera, Braconidae, Agathidinae, Agathidini) - Sharkey, Michael J.; Chapman, Eric G.; Janzen, Daniel H.; Hallwachs, Winnie; Smith, M. Alex (Zootaxa, 2015)
One previously described (Aphelagathis verticalis) and ten new species (A. bonnieirwinae, A. ceciliapinedae, A. ericgrisselli, A. genehalli, A. mclintocki, A. mikeirwini, A. rociofernandezae, A. schlingeri, A. stangei, and A. wendymooreae) are included. Aphelagathis is limited to the Nearctic and the northern part of the Neotropics. A. rociofernandezae parasitizes the caterpillars of grass-feeding Hesperiidae (Lepidoptera) as does A. verticalis.